Deadline - Sandford, John, 1944 February 23- (Sandford, John, 1944 February 23- Virgil Flowers novels, 2016)
"In Southeast Minnesota, down on the Mississippi, a school board meeting is coming to an end. The board chairman announces that the rest of the meeting will be closed, due to personnel issues. 'Issues' is correct. The proposal up for a vote before them is whether to authorize the killing of a local reporter. The vote is four to one in favor. Meanwhile, not far away, Virgil Flowers is helping out a friend by looking into a dognapping, which seems to be turning into something much bigger and uglier - a team of dognappers supplying medical labs - when he gets a call from Lucas Davenport. A murdered body has been found - and the victim is a local reporter..."--Publisher.